A contribution to the valorisation of a maritime plant: the Corema album (L.) D. Don - Ferreira, Liliana Andreia dos Santos (2019)
Corema album is an endemic maritime plant of the Iberian Peninsula that can be found in sandy dunes along the Portuguese maritime coast. The shrub and its white berries, white crowberries, have long been known, being the berries tra-ditionally harvested and consumed along the Atlantic littoral. However, alt-hough the berries are a source of nutrients and distinct from other berries because of their colour and acidic taste, they are not currently commercially exploited. The aim of this study was to contribute to the valorisation of C. album by deter-mining the nutrient profile of its berries and addressing the phytochemical po-tential of the plant by quantification of total phenolic compounds content, in par-ticular flavonoids, of extracts made with its berries and leaves. The plant showed to be a source of phenolic compounds, and the results suggest that C. album leaves extracts have a higher potential as a source of total phenolic compounds and flavonoids than the berries extracts. Another aim of this study was to determine the phytochemical potential of the plant by measuring the antioxidant activity of extracts made with its berries and leaves. The extracts have antioxidant activity, being the antioxidant activity of the leaves extracts slightly superior. The identification and quantification of phenolic compounds by HPLC was also made. From the results it was possible to verify that the berries extract con-tains trigonelline and the isomeric polyphenols 3-CQA, 4-CQA and 5-CQA and caffeic acid and the leaves extract also contains trigonelline and 3-CQA, 4-CQA and 5-CQA, and contains ferulic acid. The results show that the berries extract is a better source of caffeic acid, chlorogenic acid and its isomers, 4-CQA and 5-CQA, and the leaves extract is a better source of trigonelline and ferulic acid. With ATR-FTIR spectroscopy results was possible to identify major classes of compounds in the lyophilized berries powder and grinded leaves samples and, in the case of the berries sample, to recognize whether a particular peak or shoulder was due to the presence of seeds in the sample. Another aim of this study was to determine the anticancer activity of ex-tracts made with berries and leaves. The leaves extract showed to have a cyto-toxic effect against the HT-29 cancer cell line, inducing cell death, visible by a reduction of cell viability through the MTT assay and also by a reduction of cell proliferation through the SRB assay. Foods with the addition of white crowberries were also developed, cookies and bread, which were generally well accepted by the sensory panel of non-trained panelists to which they were submitted for sensory evaluation, showing that the development of new food products may be a way to make these berries more known to the public and start being commercialized.